Intrinsic and extrinsic dielectric responses in BiCu3Ti3FeO12 ceramics. Issue 3 (April 2015) - Shi, Pingping; Liang, Pengfei; Yang, Zhao; Yi, Jing; Ma, Chao; Chao, Xiaolian; Yang, Zupei
Abstract: BiCu3 Ti3 FeO12 ceramics with cubic perovskite-related crystal structure were prepared by a solid-state reaction method. Both the intrinsic and extrinsic dielectric responses of the ceramics are investigated. When being calcined at 800 °C and sintered at 980 °C for 20 h, BiCu3 Ti3 FeO12 ceramics are relatively dense, which exhibit a high intrinsic dielectric constant (~500 at 30 °C). Interestingly, a giant permittivity (>5000) of the ceramics is observed at high temperature, which is attributed to an extrinsic effect. Based on the results of electric impedance and modulus, it can be concluded that the giant permittivity results from the internal barrier layer capacitance effect.